The Influence of the Use of Concrete Media on the Learning Motivation of Fourth Grade Students of SD Negeri 5 Palu - Nadlrah Naimi; Hilya; Azizah; Asriani; Zulnuraini; Khairunisa; Melyani Sari Sitepu; Rita Harisma (Lembaga Bale Literasi, 2026)
This research is motivated by the low learning motivation of students in taking the science subject at SD Negeri 5 Palu. The purpose of this study is to analyze the effect of the use of concrete objects as media on the learning motivation of sixth grade students. Concrete objects as media were chosen because they are able to provide a more realistic learning experience, facilitate the understanding of abstract concepts, and encourage active student involvement in learning. This study uses a quantitative approach with a quasi-experimental method, involving two groups of students: the experimental group using concrete objects as media and the control group using conventional methods. The data collection technique was carried out by distributing a validated learning motivation questionnaire. The results of the statistical analysis showed that there was a significant difference between the learning motivation of students in the experimental group and the control group. This finding indicates that concrete objects have a positive influence on student learning motivation in science subjects. Therefore, the use of learning media that are real and contextual is highly recommended to improve the quality of learning and optimally encourage student learning interest.